RESPON TANAMAN PAKCOY TERHADAP PEMBERIAN POC REBUNG DAN MEDIA TANAM PADA HIDROPONIK SISTEM WICK - Ishak, Rizaldi Natsir; Kasifah, Kasifah; Firmansyah, Amanda Patappari; Petta Pudji, Nurson (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2024)
Pakcoy plants need nutrients like POC and organic growing media such as charcoal, cocopeat and sawdust to grow well. This research aims to determine the response of pakcoy plants (Brassica rapa L.) to various planting media with bamboo shoot POC at different concentrations, as well as the interaction between the two. This research was structured using a randomized block design (RAK) in factorial form, with the first factor being planting media using husk charcoal (M1), sawdust (M2) and cocopeat (M3), while the second factor was POC treatment which consisted of 4 doses, namely; 0 ml POC/100 ml water (D0), 20 ml POC/100 ml water (D1), 40 ml POC/100 ml water (D2), and 60 ml POC/100ml water (D3). Pakcoy plant variables observed were plant height, number of leaves, leaf area index, fresh weight of stover, wet weight of roots, and root length. The data analysis used was analysis of variance (ANOVA) with a confidence level of 95% (α 0.05) and α 0.01). If p ≥ α 0.05, then the BNJ 0.05 further test is carried out (5% confidence level). The results of the study showed that the interaction between the planting medium used and the POC dose of bamboo shoots only had a significant effect on the root length of pak choy plants in the combination of sawdust planting medium and POC 60 ml/100 ml water (M3D3), while the other parameters did not have a real impact. Partially, 99% of the best response of pakchoy plants was using charcoal husk planting medium (M1), while using POC bamboo shoots showed the best response was shown when using a POC dose of 60 ml/100 ml water.